Serum From Preeclamptic Women Triggers Endoplasmic Reticulum Stress Pathway and Expression of Angiogenic Factors in Trophoblast Cells - Castro, Karla R.; Prado, Karen M.; Lorenzon, Aline R.; Hoshida, Mara S.; Alves, Eliane A.; Francisco, Rossana P. V.; Zugaib, Marcelo; Marques, Aldilane L. X.; Silva, Elaine C. O.; Fonseca, Eduardo J. S.; Borbely, Alexandre U.; Veras, Mariana M.; et al. (Frontiers in Physiology, 2022)
Preeclampsia (PE) is a hypertensive disease of pregnancy associated with placental cell death and endoplasmic reticulum (ER) stress. It is unknown whether systemic factors aggravate placental dysfunction. We investigated whether serum factors in pregnant women with PE activate ER stress and unfolded protein responses in placental explants and trophoblast cells lineage. We cultured placental explants from third-trimester term placentas from control non-preeclamptic (NPE) pregnant women with serum from women with PE or controls (NPE). In PE-treated explants, there was a significant increase in gene expression of GADD34, CHOP, and SDF2. At the protein level, GRP78, SDF2, p-eIF2α, and p-eIF2α/eIF2α ratios were also augmented in treated explants. Assays were also performed in HTR8/Sv-neo trophoblast cell line to characterize the putative participation of trophoblast cells. In PE serum-treated, protein levels of p-eIF2a and the ratio p-elF2 α/elF2α increased after 12 h of treatment, while the gene expression of GADD34, ATF4, and CHOP was greater than control. Increased expression of SDF2 was also detected after 24 h-cultured HTR8/Sv-neo cells. PE serum increased sFLT1 gene expression and decreased PlGF gene expression in placental explants. Morphologically, PE serum increased the number of syncytial knots and reduced placental cell metabolism and viability. Analysis of the serum of pregnant women with PE through Raman spectroscopy showed changes in amino acids, carotenoids, lipids, and DNA/RNA, which may be associated with the induction of ER stress found in chorionic villi treated with this serum. In conclusion, this study provides evidence that the serum of pregnant women with PE may impact placental villi changing its morphology, viability, and secreted functional factors while triggering ER stress and an unfolded protein response. The differences between PE and control sera include molecules acting as inducing factors in these processes. In summary, the results obtained in our assays suggest that after the development of PE, the serum profile of pregnant women may be an additional factor that feeds a continuous imbalance of placental homeostasis. In addition, this study may expand the possibilities for understanding the pathogenesis of this disorder. Keywords: Placenta; Trophoblast cells; Pre-eclampsia; RE stress; UPR.